2013
DOI: 10.30935/cedtech/6089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Project-based Learning Strategy on Self-directed Learning Skills of Educational Technology Students

Abstract: Given the importance of globalization as well as the need to train skilled and knowledgeable employees for the 21 st century workforce, higher education needs to take a more critical look at the educational practices and instructional methods which lead to improvements in students' essential skills such as self-directed learning. This study sought to examine the effects of project-based learning (PoBL) strategy on students' self-directed learning skills in a system-based education course offered in the educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 15 publications
0
23
0
1
Order By: Relevance
“…Accordingly, learners achieve multiple targeted objectives, mainly with convenient classroom settings, which, in turn, translates the teacher's management skills and his/ her professional development. Since this approach, as Bagheri, Ali, Abdullah, and Daud (2013) suggest, is like a puzzle which challenges the learners in a kind of inner satisfaction through a successful learning process, where the teacher is set actively controlling and evaluating their learning constantly, the integration of PBL in the curriculum of educational technology has such ability to establish self-directed learning skills which consequently enable the learners to overcome their pedagogical needs and challenges. To this, the paper has shown that PBL aims to put the priority on the student's achievement of the project as having a crucial role in all the stages.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, learners achieve multiple targeted objectives, mainly with convenient classroom settings, which, in turn, translates the teacher's management skills and his/ her professional development. Since this approach, as Bagheri, Ali, Abdullah, and Daud (2013) suggest, is like a puzzle which challenges the learners in a kind of inner satisfaction through a successful learning process, where the teacher is set actively controlling and evaluating their learning constantly, the integration of PBL in the curriculum of educational technology has such ability to establish self-directed learning skills which consequently enable the learners to overcome their pedagogical needs and challenges. To this, the paper has shown that PBL aims to put the priority on the student's achievement of the project as having a crucial role in all the stages.…”
Section: Resultsmentioning
confidence: 99%
“…This PBL approach turns students into autonomous learners, making decisions about their research with minimal teacher guidance. Studies by Bagheri et al (2013) confirm PBL's role in fostering self-directed learning and autonomy. Swars et al (2007) argue that cooperative learning, integral to PBL, emphasizes building interdependence and group evaluation skills.…”
Section: Benefits Of Pbl Implementation (Roses)mentioning
confidence: 87%
“…The need for teachers to develop self-directed learning skills Bagheri et al (2013) as well as Du Toit-Brits (2019) argue that the increasing complexity and speed at which our environment is evolving has an effect on our daily lives and necessitates lifelong SDL. In support of this argument, Louws et al (2017a) hold that teachers are the school's most valuable assets, as they stand at the crossroads of knowledge, skills, and values transmission.…”
Section: 2mentioning
confidence: 99%